2007
DOI: 10.1055/s-2006-945102
|View full text |Cite
|
Sign up to set email alerts
|

An endoscopically implantable device stimulates the lower esophageal sphincter on demand by remote control: a study using a canine model

Abstract: The LES pressure can be increased using an on-demand microstimulator. The implantation procedure is minimally invasive, represents a novel therapeutic approach to gastroesophageal reflux disease, and may have therapeutic potential for other gastrointestinal motility disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Clark et al [34] reported a rise in LES pressure in dogs by using an on demand microstimulator, which was implanted endoscopically. Though, 8 mA or more had to be applied to achieve desired pressure increase.…”
Section: Endoscopic Antireflux Proceduresmentioning
confidence: 99%
“…Clark et al [34] reported a rise in LES pressure in dogs by using an on demand microstimulator, which was implanted endoscopically. Though, 8 mA or more had to be applied to achieve desired pressure increase.…”
Section: Endoscopic Antireflux Proceduresmentioning
confidence: 99%
“…The technique has been shown to increase LES resting pressure in animal models [100][101][102]. Human studies, however, focused primarily on patients with EE who are on PPI treatment and have low resting LES pressure as well as abnormal 24-h esophageal acid exposure [103,104].…”
Section: The Les Stimulation System (Endostim)mentioning
confidence: 99%
“…The technique has been shown to increase LES resting pressure in animal models. [51][52][53] Human studies, however, focused primarily on patients with EE who are on PPI treatment and have low resting LES pressure as well as abnormal 24-hour esophageal acid exposure. 54,55 The authors demonstrated that short-term electrical stimulation of the LES improved LES resting pressure, esophageal acid exposure, GERD-HRQL, and PPI consumption without affecting the amplitude of esophageal peristalsis or LES relaxation.…”
Section: The Les Stimulation System (Endostim)mentioning
confidence: 99%